Dissecting Loneliness in the Digital Age: An Insight into the Experiences of Medical Students Amid and Beyond the COVID-19 Pandemic [version 2; peer review: 1 approved, 2 approved with reservations] - Abdulqadir J. Nashwan; Nour Abu Afifeh; Rawan Alahmad; Ghazi Abu Afifeh (F1000Research)
This narrative review explores loneliness among medical students, particularly heightened during the COVID-19 pandemic. This review aims to narratively describe how the digital age, both pre- and post-pandemic, influences loneliness and to assess the psychological effects of the pandemic on medical students. Our literature search, adhering to SANRA guidelines, scrutinized studies published in the last ten years focusing on loneliness among medical students. Our findings reveal that medical students experienced significant loneliness during the pandemic, attributed to virtual learning environments and decreased social interactions. Notably, the transition to online education has mitigated and exacerbated feelings of isolation. The review also highlights the dual role of social media in either alleviating or intensifying loneliness, depending on usage patterns and platform types. Overall, our study underscores the need for targeted interventions and support systems to address the mental well-being of medical students in the digital age and beyond, providing crucial insights for future research and policy-making in educational and psychological support frameworks.